Two simple techniques for hysteresis power losses measurement - Bianchi, Inacio [UNESP]; da Silva, Marcela Frank [UNESP] (IEEE, 2007)
This paper presents two methods to measure magnetic losses in an iron core for didactic applications for undergraduate students. It is based on indirect measurements of magnetic field and induced flux, simplifying the required instrumentation, and thus, making its implementation possible for lab sessions. Moreover, a comparison between two methods is proposed, allowing the students reaching a deeper understanding of the hysteresis phenomena.
Keywords: hysteresis; magnetic core losses; magnetic fields; transformers cores